Effectiveness of an R-based software to detect closed-loop cardiovascular interactions and baroreflex impairment in human subjects from the EUROBAVAR data set - Chao-Écija, Álvaro; Carrasco-Gómez, Daniel; Dawid-Milner, Marc Stefan (My University, 2022)
We recently developed an R-based software that could model closedloop cardiovascular interactions. In this study, we applied this tool on the EUROBAVAR data set to further test its applicability. The aim of this work is to test the effectiveness of our software to identify cardiovascular regulatory mechanisms and baroreflex impairment from these data. We first uploaded each recording into our software to model the interactions present between systolic blood pressure (SBP) and IBI by employing a wavelet detrending and multivariate autoregressive modeling algorithm. Then, our software estimated causal coherence and Gaussian-weighted baroreflex sensitivity (BRS) indexes from each model at the low frequency (LF, 0.04-0.15 Hz, sympathetic) and high frequency (HF, 0.15-0.4 Hz, parasympathetic) bands. Immediate variability transfer from SBP to IBI was also computed for each subject. Our results showed that, when standing, the estimates of only two subjects, B005 and B010, were below percentile P10 of the BRS distribution (0.719 ms/mmHg at HF, 1.678 ms/mmHg at LF) at both bands. A literature review indicated that these two subjects had a baroreflex impairment. In non-baroreflex-impaired subjects, causal coherence from IBI to SBP at LF was significantly predominant at rest when compared with the coupling from SBP to IBI (p < 0.001). This predominance disappeared during standing due to changes in the couplings, suggesting a baroreflex interaction. Closed-loop BRS supineto- standing ratios in these subjects were 1.69 ± 0.93 (LF band) and 3.1 ± 1.32 (HF band), showing a significantly decreased BRS during standing position (p < 0.01, LF; p < 0.001, HF). Immediate transfer also decreased during standing (p < 0.001). In conclusion, our software managed to evaluate causal closed-loop interactions between cardiovascular variables from the data set, evidencing a baroreflex coupling, Thus, this allows it to be a useful tool for baroreceptor evaluations.
Keywords: Sistema cardiovascular; Cardiovascular regulation; Baroreflex impairment; Spectral analysis; Autoregressive models